The Role of Accountants in Climate Change in the Cement Industry in Indonesia: Net Zero Emissions Movement 2060 - Yanuar Ramadhan; Cita Restuningsih; Alifia Nur Haristi; Muh Gaus; Sandy Sandy; Dewi Siswanti Sulim (Pelopor Publikasi Akademika, 2023)
The target of this study discusses the Role of Accountants on Climate Change related to Net Zero Emissions 2060 in the Cement Sub-Sector Industry in Indonesia. This study uses narrative analysis that describes the causes of climate change, the impact on company finances and accountants' efforts in dealing with field conditions. This study found that if the accounting profession can function dominantly covering various climate change issues, its function is to force all accountants to contribute to helping the government meet the target of the Net Zero Emissions 2060 movement by internalizing climate change issues in financial statements, assisting company management in making sustainable strategy planning, measuring environmental impacts and developing carbon emission reduction strategies. The conclusion of this study is companies registered in the cement sector industry in general have supported the Indonesian government's program in the Net Zero Emission 2060 movement. This is evidenced by the activities and activities they carry out in sustainability reports and corporate social responsibility activity reports